The “San Francisco” tourist pedagogical farm product as a natural learning environment to enhance skills with performance criteria - Burbano Pulles, Marco Rubén; Iturralde Vallejos, Jaime Alejandro; Guevara Guevara, Elizabeth Josefina; Chandi Yépez, Alonso Javier (SATHIRI, 2020)
This research sought to establish the functionality of the pedagogical tourist product made in the "San Francisco" Experimental Farm that belongs to UPEC as a natural learning environment for the development of skills with performance criteria. It started from the diagnosis of all the resources that the farm had at that time, through an observation form its components were evaluated and it was establish its applicability as spaces for the natural environment. In addition, the skills with performance criteria of the current national basic general education curriculum of the third and fourth year Natural and Social Sciences subjects were identified in order that the recognized spaces can be improved through the incorporation of new resources according with  the skills that were assessed. Finally, with the intention of evaluating the impacts of the study, two elementary schools of Tulcán city were chosen through a questionnaire applied before and after the visit to the tourist product, demonstrating an improvement in their skills with performance criteria of a 4.87% in natural science and 13.32% in social studies for the third years of basic education and 20.53% in natural science and 14.30% in social studies for the fourth year of basic education.
Keywords: Natural learning environment; skills with performance criteria; tourism and education; experimental farm